Multiscale polyethylene fiber - nanocellulose fiber composites through laser fusion and bacterial in situ synthesis - Schlicht, Samuel; Wesinger, Mara; Kaufmann, Anke; Rösel, Uta; Fischer, Dagmar; Drummer, Dietmar (Conference of the Polymer Processing Society 2024, 2024)
Ultra-high molecular weight polyethylene (PE-UHMW) fibers and bacterial nanocellulose (BNC) fibers both display exceptional mechanical properties alongside the outstanding tribological properties of PE-UHMW while showing an unrestricted biocompatibility. For combining the intrinsic advantages of both materials, the present work demonstrates an approach that integrates the slurry-based laser fusion of PE- Polyvinylpyrrolidone (PE-PVP) composites and the subsequent bacterial biosynthesis of nanoscopic cellulose fibers. PE-PVP composites exhibiting a fraction of 10% of PEUHMW fibers with a mean length of 5.0 mm were obtained through the locally selective, laser-based layer-wise evaporation and subsequent sintering of aqueous suspensions, yielding long fiber composites with a water-soluble matrix. The in situ synthesis of bacterial nanocellulose exploits the gelling and dissolving of high-molecular PVP in aqueous media, promoting the dispersion of individual fibers. Through the infiltration of the PE-PVP composite with nanocellulose-forming Komagataeibacter xylinus and the subsequent bacterial synthesis of BNC, a multiscale composite of PE- UHMW fibers and BNC fibers was obtained, corroborating the infiltration of micrometer-scale PE fiber composites with nanoscale cellulose fibers, yielding a nanoporous multiscale composite. Release experiments using methylene blue confirmed the potentials of PE-BNC composites for drug delivery applications, showing a sigmoidal release similar to pure nanocellulose.<br